(untitled) (Revista Rupturas, 2025)
This study analyzes the transition from cash transfers to the Minimum Living Income (MMI) in Mexico, assessing its viability and challenges. It shows how the economic policies of recent decades have exacerbated inequality and precarious work, leading to the need to expand cash transfers. It highlights the evolution of social programs from a welfare approach to the consolidation of rights. Although the MVI is recognized in the Constitution of Mexico City, its implementation at the national level remains uncertain, with debates on financing and its impact on income redistribution and the labor market. However, its importance in reducing poverty and inequality, especially for the most vulnerable groups, is recognized.